2018
DOI: 10.1097/gox.0000000000001987
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Oncoplastic Breast Conservation: Combining Autologous Volume Replacement and the Wise-pattern Mammaplasty

Abstract: Background:Oncoplastic breast-conserving surgery describes a set of techniques that allow for generous oncological resection with immediate tumor-specific reconstruction. These techniques are classically divided into either volume displacement (local breast flaps and or reduction mammaplasty/mastopexy strategies) versus volume replacement strategies (transfer of autologous nonbreast tissue from a local or distant site and, less commonly, implant placement). There have been few descriptions of merging these 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Cadaveric dissections have demonstrated that lateral intercostal artery perforator is found between 2.6 and 3.5 cm anterior to the anterior border of latissimus dorsi which is the area between anterior and mid‐axillary line. Hamidi et al in their follow‐up study detailed that dominant perforator to the flap is consistent in its location and is found commonly in sixth and seventh intercostal space 2.5–3.5 cm from anterior edge of latissimus dorsi muscle [3, 12]. In our entire study, we preserved the tissue in the said area and found that it was 100% effective and safe for the viability of the flap and we did not have any partial or complete flap loss.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaveric dissections have demonstrated that lateral intercostal artery perforator is found between 2.6 and 3.5 cm anterior to the anterior border of latissimus dorsi which is the area between anterior and mid‐axillary line. Hamidi et al in their follow‐up study detailed that dominant perforator to the flap is consistent in its location and is found commonly in sixth and seventh intercostal space 2.5–3.5 cm from anterior edge of latissimus dorsi muscle [3, 12]. In our entire study, we preserved the tissue in the said area and found that it was 100% effective and safe for the viability of the flap and we did not have any partial or complete flap loss.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the author published the first description of combining autologous VR and Wise-pattern VD for challenging cases of oncoplastic breast-conserving surgery. 12 That report described combining a Wise-pattern mastopexy and an extended lateral intercostal artery perforator (LICAP) flap to harvest tissue from the back to reconstruct defects regardless of their breast location. We have since abandoned the extended LICAP flap for the muscle-sparing latissimus dorsi (MSLD) flap, which has superior blood flow, when such large volumes are required for VR.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 For women with small breasts and adequate local tissue, autologous volume augmentation is often required when a large amount of gland is removed. 4 Current options for autologous volume augmentation include the thoracodorsal artery perforator (TDAP) flap, the spiral flap, and serial fat grafting. Among the current techniques, the LICAP flap provides benefits of repurposing local tissue by addressing axillary tissue excess, while maintaining a reliable tissue source due to its robust blood supply.…”
Section: Introductionmentioning
confidence: 99%